A highly spatially resolved GIS-based model to assess the isoprenoid emissions from key Italian ecosystems - Pacheco, Claudia Kemper; Fares, Silvano; Ciccioli, Paolo (Atmospheric Environment, 2014)
The amount of Biogenic Volatile Organic Compounds (BVOC) emitted from terrestrial vegetation is of great importance in atmospheric reactivity, particularly for ozone-forming reactions and as condensation nuclei in aerosol formation and growth. This work presents a detailed inventory of isoprenoid emissions from vegetation in Italy using an original approach which combines state of the art models to estimate the species-specific isoprenoid emissions and a Geographic Information System (GIS) where emissions are spatially represented. Isoprenoid species and basal emission factors were obtained by combining results from laboratory experiments with those published in literature. For the first time, our investigation was not only restricted to isoprene and total monoterpenes, but our goal was to provide maps of isoprene and individual monoterpenes at a high-spatial (∼1 km2) and temporal resolution (daily runs, monthly trends in emissions are discussed in the text). Another novelty in our research was the inclusion of the effects of phenology on plant emissions. Our results show that: a) isoprene, a-pinene, sabinene and b-pinene are the most important compounds emitted from vegetation in Italy; b) annual biogenic isoprene and monoterpene fluxes for the year 2006 were ∼31.30 Gg and ∼37.70 Gg, respectively; and c) Q. pubescens+Q. petrea+Q. robur, Q. ilex, Q. suber and Fagus sylvatica are the principal isoprenoid emitting species in the country. The high spatial and temporal resolution, combined with the species-specific emission output, makes the model particularly suitable for assessing local budgets, and for modelling photochemical pollution in Italy.
Keywords: BVOC inventory; isoprene; Isoprenoids; Italian forests; Monoterpenes